Correlation between regional cerebral blood flow and brain atrophy in dementia. Combined study with 133Xenon inhalation and computerised tomography. Issue 10 (October 1978) - Melamed, E; Lavy, S; Siew, F; Bentin, S; Cooper, G
Abstract : Measurement of the regional cerebral blood flow (rCBF) by the 133Xenon inhalation method and computerised tomography were performed in 25 patients with presenile and senile dementia. Reduction of rCBF and various degrees of ventricular enlargement and cortical sulcal widening were demonstrated in the majority of demented subjects. However, there was no correlation between rCBF values and the severity of ventricular dilatation or cortical atrophy. These findings suggest that loss of brain substance is not an important factor in the reduction of rCBF in dementia.